2002
DOI: 10.1042/0264-6021:3630377
|View full text |Cite
|
Sign up to set email alerts
|

The Aspergillus niger faeB gene encodes a second feruloyl esterase involved in pectin and xylan degradation and is specifically induced in the presence of aromatic compounds

Abstract: The faeB gene encoding a second feruloyl esterase from Aspergillus niger has been cloned and characterized. It consists of an open reading frame of 1644 bp containing one intron. The gene encodes a protein of 521 amino acids that has sequence similarity to that of an Aspergillus oryzae tannase. However, the encoded enzyme, feruloyl esterase B (FAEB), does not have tannase activity. Comparison of the physical characteristics and substrate specificity of FAEB with those of a cinnamoyl esterase from A. niger [Kro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
79
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 94 publications
(87 citation statements)
references
References 33 publications
8
79
0
Order By: Relevance
“…28 No amino acid sequence predicted from ORF3 exhibited signifi cant homology to those of published genes, including tannase. 29,30 To identify the gene for tannase, we constructed deletion derivatives of pTZtan18 and subcloned ORF2 and ORF3; production of tannase in the strain carrying the plasmid was tested (Fig. 1).…”
Section: Cloning and Characterization Of A Gene For Tannase In S Lugmentioning
confidence: 99%
“…28 No amino acid sequence predicted from ORF3 exhibited signifi cant homology to those of published genes, including tannase. 29,30 To identify the gene for tannase, we constructed deletion derivatives of pTZtan18 and subcloned ORF2 and ORF3; production of tannase in the strain carrying the plasmid was tested (Fig. 1).…”
Section: Cloning and Characterization Of A Gene For Tannase In S Lugmentioning
confidence: 99%
“…The molecular masses of FAEs of the white rot fungi P. eryngii and P. sapidus are 67 kDa and 55 kDa, respectively, which are higher than those of the FAEs of A. awamori (35 kDa) (176) and A. niger FaeA (36 kDa) (177,178) but lower than that of A. niger FaeB (74 kDa) (178). P. eryngii FaeA (PeFaeA) and P. sapidus Est1 are 93% similar at the amino acid sequence level (173).…”
Section: Hemicellulose-and Pectin-debranching Enzymesmentioning
confidence: 99%
“…Work performed since then on the effects of CREA on xylanolytic genes has demonstrated that carbon source concentrations of around 1% cause significant reductions in expression levels due to CREAmediated repression (de Vries et al 1999). In addition, a recent study demonstrated that glucuronic acid causes CREA-mediated repression of the induction by ferulic acid of feruloyl esterase-encoding genes from A. niger (de Vries et al 2002). Therefore, in this study, lower carbon source concentrations were used and it is thus not surprising that no aguA expression was previously detected in a wild-type strain using 1% glucuronic acid.…”
Section: Discussionmentioning
confidence: 79%